Qualitative changes of motoric abilities at soccer players under the effects of situational soccer training - Colakhodzic, E.; Rado, I.; Mahmutovic, I.; Skender, N. (Homosporticus, 2008)
The aim of this research conducted on a sample of 75 soccer players aged 12 to 15, was to specify qualitative changes occurring due to programmed soccer training process. The programme, having been based on situational problem solution through game in all phases of training, lasted six months and it included 72 training units and 8 league games. The span of this research covers detection of effects of programmed training activity in the field of motoric abilities of soccer players aged 12-15, and than to detect the essence of these changes. The results can serve as a guideline for enhancement and correction of mistakes in planning and programming future training units in work with this age group of young players. Factor analysis is used in the process of determination of qualitative changes - method of congruency (compliance of factor scores). Based on the factor analysis, we can conclude that systematic qualitative changes have occurred under the effect of structured soccer programme. In the basic structure of motoric dimensions, after completing factorization of the initial measuring, six latent dimensions were determined, explaining 65.7% of the overall variability. After completion of the soccer programme we conducted factor analysis of the results provided with final measuring and it can be concluded that reduction and condensation of latent dimensions appears since we got five latent dimensions explaining 63% of the overall variability. The analysis has shown that through the course of time of implementation of the project, motoric dimensions had restructured taking up a different position. Their structure isn`t as dispersed as in initial measuring, as certain form of condensation took place, so that the motoric abilities entered a more orderly relation, for which the credit can be given to programmed soccer procedure.